PENGGUNAAN INFORMATION COMMUNICATION AND TECHNOLOGY (ICT) TOOLS DALAM MENDUKUNG PEMBELAJARAN MATEMATIKA INTERAKTIF - Sulistiawati Sulistiawati; Yaya S. Kusumah; Jarnawi A. Dahlan (IKIP Siliwangi, 2021)
The current era has arrived at the presence of a young generation called digital native so that interactive learning based on Information Communication and Technology (ICT) in mathematics is considered very suitable for this situation. This study aims to find out: 1) how is the development and use of ICT tools in interactive mathematics learning in the last decade?, and 2) what are the opinions of users of ICT tools in learning mathematics?. The method used in this research is a literature study method, by reviewing literature or scientific papers relevant to the research problem by using scientific sources. The results of this study are: 1) the development and use of ICT equipment in interactive mathematics learning within the last decade to the use of high technology including teachers using videos, general ICT software, and mathematics ICT software: Computer Algebra System, Dynamic Geometric Software, Dynamic Mathematics Software and Augmented Reality (AR) as part of Virtual Reality (VR); and 2) ICT users in learning (teachers and students), especially mathematical software, have a positive response in the use of ICT in learning.